Workplace ethics: Instilling safety factors in the palm oil manufacturing industry - Zaleha, Kadil; Mohd Ghazali, Maarof (Penerbit Universiti Malaysia Pahang, 2024)
The purpose of this study is to look at factors influencing manufacturing workplace safety in the palm oil manufacturing industry. Workplace safety encompasses a set of practices, policies, and procedures designed to create a safe and healthy work environment for employees. The study was conducted using quantitative data and was distributed to respondents using an online platform. The respondent of this study is 68 manufacturing workers. There were three parts to the questionnaire that assessed safety training, management commitment and workplace safety. The data was analysed using Smart PLS and SPSS. The results from this research reveal that both independent variable safety training and management commitment have a positive relationship to workplace safety. The result demonstrates how safety programs help employees learn how to perform their jobs correctly, maintain workplace safety, and reinforce existing safety procedures. The result of this study has further acknowledged the importance of management commitment towards the success of any safety performance.